On the question of development of the institute of “tax obligation” in the conditions of the digitalization of the economy - O. I. Lyutova (Правоприменение, 2022)
The subject. The analysis of trends in the development of the institution of tax liability, which arise as a result of digitalization of the economy.The purpose of the article is to identify trends in the development of the science of tax law and tax legislation in relation to the theoretical category “tax obligation” and the legal regulation of individual duties of taxpayers.The research methodology includes an analysis of regulatory acts of tax legislation governing the issues of generally binding tax obligations, as well as the obligation to pay tax and submit tax returns.The main results and scope of their application. The active use of information and communication technologies in tax relations necessitates a theoretical assessment of the possible transformation of the central category of tax law - tax liability.This will eliminate the unnecessarily complicated process of notifying the tax authorities about such transactions, which is currently being carried out simultaneously by the operators of electronic platforms and the taxpayers themselves. This will make it possible to develop an opinion on the development of legal regulation of various duties of taxpayers, which are fulfilled in the context of digitalization.Conclusions. The author proves the static nature of the content of the concept of tax liability, which is a system of its features. The “classic” sign of general obligation inherent in the tax obligation has been questioned as a result of the ambiguous legal regulation of the tax on professional income. According to the author, in this regard, it is necessary to clarify the legal status of the self-employed in terms of their recognition or non-recognition as entrepreneurs. It is also necessary to improve the legal regulation of the use of a single tax payment and the issue of the gradual abandonment of tax reporting. Such norms should appear if the tax authorities have the technical ability to move to a new stage of digitalization.